UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI MODERASI BERAGAMA DI SMK YAPIS TEMINABUAN - Sahril Soean; Indria Nur; Ismail Suardi Wekke (Pascasarjana IAIN Sorong, 2022)
This study aims to describe the forms of religious moderation values and the efforts of PAI teachers in instilling religious moderation values at YAPIS Teminabuan Vocational School. Sources of data are primary data sourced from school principals, vice principals, teachers, and students. While secondary data are taken from documents that have anything to do with research. Collecting data through observation, interviews, and documentation. The results of the study show that religious moderation at YAPIS Teminabuan Vocational School is contained in the values of national commitment, tolerance, anti-violence, and accommodation of local culture. Efforts to instill the values of religious moderation at YAPIS Teminabuan Vocational School apply several methods, namely; first, the learning method in the classroom. Second, extracurricular activities. Third, habituation activities. Habits in the school environment such as reading the Koran, giving opportunities to followers of other religions if they want to worship, and carrying out community service in the school environment which is carried out by all school members